Gambaran Penilaian Status Malnutrisi dan Lama Rawat Inap Pasien Hipertensi di RSUD Ir. Soekarno Sukoharjo - Andi Kurniawan; Rusjiyanto Rusjiyanto (Universitas Muhammadiyah Semarang, 2019)
Hypertension disease in Indonesia are increasing every year. Manifestation of hypertension’s symptom can affect to malnutrition status and indirectly affect to length of stay. The objective of this research to know the overviews of malnutrition and length of malnutrition and length of stay of hypertension patient at RSUD Ir. Soekarno, SukoharjoThe research description research with observational approach andcross sectional study design. The sampling techniqueused is consecutive sampling as much as 24 respondents. The assessment of malnutrition using Subjective Global Assessment, while the patient’s length of stayis obtained by calculating the difference between date of attendance and date of left the hospital. Respondent with female gender is 58,9%. Most respondents are middle age (50%). Level of education elementary school is 41% respondents. The job of respondents 41% are labor. Respondent with hypertension stage 2 with length of stay are 52%. Hypertension stage 2 respondent with length of stay that classified medium as much as 52%. Respondent’s nutritional status that classified as bad nutrition 10,5% and poor nutrition 21,2%. The majority of SGA score of patients is A or not malnutrition.Keywords : Hypertension, Malnutrition, Length of Stay